MICROEMULSION FORMULATION OF ALOE VERA GEL AND APIUM GRAVEOLENS ETHANOL EXTRACT FOR OPTIMIZING HAIR GROWTH PROMOTION - Pamudji, Jessie Sofia (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: Follicular penetration of hair promotion substances to the bulge region is needed to potentiate cell proliferation and hair shaft lengthening. Nano-size globule is one of important delivery systems applied for hair follicle targeting. This research aims to explore the effect of microemulsion on hair promoting activities of a mixture of hydrophilic substances of Aloe vera gel and semipolar substances of Apium graveolens ethanolic extract. Methods: The clear water in oil (W/O) and oil in water (O/W) microemulsions were developed by constructing phase diagram of various ratios of Crodamol GTCC, Croduret 50 SS, glycerin/alcohol, and water. A. vera (1%) and celery extract (2%) were incorporated during microemulsion preparation. The microemulsions were applied over shaved skin areas of the backs of Wistar rats, and the average length of 10 hair samples was determined at day 7, 14, and 21 compared to the un-treated area. The weight of hair/cm2 area was also analyzed at day 21. Hair growth promotion of the microemulsions was compared to the other groups of rats applied by A. vera in water (AVW), celery extract in water and oil (CEW and CEO), and combination of A. vera and celery extract in water (AVCEW). Result: The W/O and O/W microemulsion consisted of globules at the average size of 61.7 and 81.5 nm, respectively, which showed stable size following six cycles of freeze-thaw. The W/O microemulsion increased hair growth dramatically started at day 7 (220%) and day 14 (275%) and slowed-down at day 21 (163%) with similar profile shown by AVW (74.5, 65.8, 31.7%, respectively). On the contrary, the hair growth promotion of O/W microemulsion delayed to day 14 but maintained till day 21 (143.7, 214.5, 171.9 at day 7, 14, and 21, respectively) with similar profile shown by CEW and CEO. Hair densities were also doubled in the areas treated by both microemulsion types than in the areas treated by a combination of AVCEW in water. Conclusion: Incorporation of hydrophilic and semipolar substances of hair growth promoter in nano-size globules of W/O and O/W microemulsions lead to pilosebaceous targeting and optimize the growth promotion activities. Keywords: Aloe vera, Apium graveolens, Water in oil microemulsion, Oil in water microemulsion, Hair growth, Pilosebaceous.